Transition metal doped iron-containing solid waste catalytic material as well as preparation method and application thereof in degradation of PET (Polyethylene Terephthalate)

By using Fe3O4 ferrite catalyst doped with transition metals, the problems of high cost and low efficiency of PET alcoholysis catalysts have been solved, realizing the efficient recycling of PET and the high-value utilization of solid waste. The catalyst is magnetic and easy to separate.

CN121103360APending Publication Date: 2025-12-12SHENZHEN UNIV

Patent Information

Application Number
CN202511307553.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-14
Publication Date
2025-12-12

Smart Images

  • Figure CN121103360A_ABST
    Figure CN121103360A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high-valued utilization of solid wastes, and discloses a transition metal doped iron-containing solid waste catalytic material, a preparation method thereof and an application of the transition metal doped iron-containing solid waste catalytic material in degradation of PET (Polyethylene Terephthalate). The method comprises the following steps: carrying out physical screening or disc (ball) milling treatment on the iron-containing solid waste, then dissolving the iron-containing solid waste in organic acid, and heating and stirring to obtain turbid liquid; carrying out solid-liquid separation on the turbid liquid to obtain a solid; dissolving transition metal salt in water, adding the transition metal salt and the solid into a reaction container, adding oxalic acid, adjusting the pH value, and uniformly stirring and mixing; carrying out heating reaction on the mixed solution, and drying an obtained reaction product to obtain a precursor; and roasting the precursor to obtain the transition metal doped ferrite catalyst. The method for preparing the PET alcoholysis efficient catalyst from the iron-containing solid waste has the advantages of being low in raw material cost, high in catalytic efficiency, low in equipment requirement, easy to separate and recycle and the like, a brand new thought is provided for PET alcoholysis, the method has a large application prospect, and the catalytic material is suitable for industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-value utilization of solid waste, specifically to the preparation method and application of transition metal-doped iron-containing solid waste PET degradation catalytic materials. Background Technology

[0002] Plastics are widely used in food packaging, construction, and other fields due to their low cost, lightweight nature, and excellent chemical stability. Among them, polyethylene terephthalate (PET), a polyester plastic synthesized from terephthalic acid and ethylene glycol, has become one of the most widely used commercial plastics globally, with an annual production of up to 50 million tons, thanks to its outstanding thermal stability, transparency, and lightweight properties. However, the current recycling rate of PET plastic is less than 10%, resulting in large amounts of waste PET plastic accumulating in landfills or marine environments (microplastics), posing a serious threat to human health and the marine ecosystem. Against this backdrop, promoting the green degradation and recycling of PET has become a critical issue that urgently needs to be addressed.

[0003] Currently, the main methods for chemical recycling of PET include hydrolysis, methanol alcoholysis, ethylene glycol alcoholysis, and other chemical depolymerization methods. Research on PET ethylene glycol alcoholysis catalysts primarily focuses on systems such as ionic liquids, metal acetate catalysts, and metal oxide catalysts. These catalysts generally suffer from high preparation costs, poor catalytic stability, and potential environmental pollution risks. Therefore, there is a need to develop novel PET alcoholysis catalysts that are low-cost, stable, and exhibit excellent catalytic activity. Thus, the development and preparation of heterogeneous catalysts is essential for facilitating recovery and separation. Heterogeneous catalysts are often prepared using amphoteric oxides with certain ionic bonds. However, these oxides are prepared from pure metal salt precursors, resulting in high chemical reagent costs, low catalytic activity, and poor durability due to lack of modification, severely limiting the efficiency and market application of PET alcoholysis.

[0004] Iron-containing solid waste refers to solid waste slag rich in iron compounds generated during industrial processes such as iron smelting and machinery manufacturing. It mainly includes blast furnace slag, red mud, ferroalloy slag, and scrap iron and steel. The large-scale stockpiling of this iron-containing solid waste not only occupies land resources but also poses a serious threat to the ecological environment. In recent years, Fe3O4, as an environmentally friendly and non-toxic magnetic transition metal oxide, has shown broad application prospects in the field of catalytic materials. Therefore, how to efficiently utilize iron-containing solid waste to prepare high-performance PET alcoholysis catalysts, thereby reducing catalyst production costs and achieving high-value utilization of solid waste, has become a key technical challenge that urgently needs to be overcome in this field.

[0005] Chinese invention patent application "A metal oxide catalyst for alcoholysis of PET and its preparation method and application" (CN119588363) discloses a method for preparing a catalyst by loading a mixture of active components MgO and ZnO onto metal oxides of Fe and Bi, and synthesizing it through co-precipitation and rotary evaporation impregnation. Although the yield of terephthalate (BHET) is over 80%, the active components MgO and ZnO in this invention are both prepared from pure metal salts, resulting in high raw material and reagent costs, and a calcination temperature of 700℃, making the preparation cost too high and difficult to commercialize. Summary of the Invention

[0006] To address the drawbacks of high raw material costs and low catalytic efficiency associated with heterogeneous catalysts (metal oxides) in traditional PET alcoholysis systems, this invention provides a method for preparing a transition metal-doped catalytic material for the degradation of PET from iron-containing solid waste, and its application. This invention utilizes iron-containing solid waste to prepare a highly efficient PET alcoholysis catalyst, offering advantages such as low raw material costs, high catalytic efficiency, low equipment requirements, and easy separation and recovery. It provides a novel approach to PET alcoholysis and has significant application potential. The catalytic material of this invention is suitable for industrial application.

[0007] The technical solution of this invention is as follows.

[0008] A method for preparing a transition metal-doped iron-containing solid waste catalytic material includes the following steps: (1) Physically screen or treat the iron-containing solid waste by disc (ball) milling, then dissolve it in organic acid, heat and stir until no more precipitate is formed, and obtain a suspension; (2) The suspension obtained in step (1) is subjected to solid-liquid separation, and the resulting solid is washed and dried for later use; (3) Dissolve the transition metal salt in water and add it to the reaction vessel with the solid obtained in step (2) at a transition metal M / iron molar ratio of 1:1~3. Add oxalic acid, adjust the pH to 2~4, and then stir and mix evenly. (4) The mixture from step (3) is heated to react, and the resulting reaction product is dried to obtain the precursor; (5) The precursor obtained in step (4) is placed in a muffle furnace for calcination to obtain a transition metal-doped ferrite catalyst.

[0009] In the above method, in step (1), the iron content in the iron-containing solid waste is expressed as Fe2O3 ≥ 10 wt.%; the iron-containing solid waste includes one or more of steel slag, red mud, blast furnace slag, ferroalloy slag, iron-containing catalysts, and scrap steel.

[0010] In the above method, in step (1), the organic acid is one of acetic acid, oxalic acid or citric acid; the heating and stirring is at 20~80℃ and the stirring rate is 5~100 rpm / min.

[0011] In the above method, in step (2), the drying is performed at a temperature of 100±5℃ for 12~48h.

[0012] In the above method, in step (3), the transition metal salt is Mn-containing... 2+ Cr 3+ Zn 2+ Cu 2+ or Co 2+ Metal salts.

[0013] In the above method, in step (4), the heating reaction is carried out at 20~95℃ with a stirring rate of 50~200rpm / min for 6~24h.

[0014] In the above method, in step (5), the roasting temperature is 200~600℃ and the roasting time is 1-10h.

[0015] A transition metal-doped catalytic material for iron-containing solid waste is disclosed. The catalytically active component is a multi-component composite metal oxide composed of ferrite and transition metal. A catalytic material supported on silica and alumina is also disclosed, with the weight ratio of the three components being 1:0.3–0.8:5–10. In this catalytic material, the transition metal ions alter the electronic structure of the ferrite, creating oxygen vacancies. The silica and alumina synergistically enhance the catalytic activity of the ferrite. The ferrite primarily exists in the form of Fe3O4, while the transition metal exists in the form of its corresponding oxide. It should be noted that the multi-component composite metal oxide composed of ferrite and transition metal is not a simple mixture of metal oxides.

[0016] A transition metal-doped iron-containing solid waste catalytic material is applied to the degradation of PET, comprising the following steps: adding the transition metal-doped iron-containing solid waste catalytic material, waste PET plastic and ethylene glycol into a reaction vessel for depolymerization and transesterification reaction, heating to 150~200℃, and stirring at a constant temperature for 1~6h to obtain the diethyl terephthalate (BHET) reaction product.

[0017] In the above applications, the mass ratio of the transition metal-doped iron-containing solid waste catalytic material to waste PET plastic is 0.02~0.3:1, and the mass ratio of the waste PET plastic to ethylene glycol is 1:1~10.

[0018] The mechanism of this invention is as follows: A magnetic catalyst, Fe3O4, is prepared using iron-containing solid waste as a substrate. By replacing divalent / trivalent Fe ions with transition metal ions, the electronic structure of the ferrite (MFe2O4, where M is a transition metal element) is altered, creating oxygen vacancies and increasing catalytic active sites. Furthermore, common iron-containing solid wastes, such as steel slag, red mud, and blast furnace slag, contain large amounts of silica and alumina. During the preparation of the ferrite catalyst, under hydrothermal reaction conditions, an aluminum silicate (SiO2-Al2O3) support is formed, synergistically enhancing the ferrite catalytic activity. PET alcoholysis follows a nucleophilic substitution mechanism. When using a catalyst with Lewis acid sites on metal oxides, metal ions can attack the carbonyl oxygen on the PET chain, thereby polarizing the C-O bond, enhancing the electrophilicity of the carbonyl carbon, promoting the nucleophilic attack of the carbonyl carbon by the hydroxyl groups in ethylene glycol, cleaving the ester bonds of PET, and ultimately generating BHET monomers. In addition, during the post-separation process, the transition metal-doped ferrite is magnetic and can be efficiently separated from the reaction products using a magnet.

[0019] Compared with the prior art, the advantages of this invention are: (1) This invention innovatively uses iron-containing solid waste to prepare PET alcoholysis catalyst, which reduces the preparation cost of catalyst and effectively solves the problem of iron-containing solid waste treatment and disposal, realizing the high-value utilization of solid waste.

[0020] (2) The present invention uses transition metal doped ferrite, which increases the number of catalytic active sites by increasing oxygen vacancies, thereby effectively improving the catalytic activity of ferrite.

[0021] (3) The transition metal doped ferrite catalyst prepared by the present invention has magnetic characteristics and can be separated from the catalyst and reaction products simply and efficiently by means of adsorption by magnet. Attached Figure Description

[0022] Figure 1 This is a flowchart illustrating the preparation method of the transition metal-doped iron-containing solid waste PET degradation catalytic material of the present invention and its alcoholysis application.

[0023] Figure 2 This is a schematic diagram of the chemical reaction mechanism and PET alcoholysis mechanism of the transition metal-doped iron-containing solid waste catalyst prepared in this invention. Detailed Implementation

[0024] This invention provides a method for preparing a transition metal-doped iron-containing solid waste PET degradation catalytic material and its application. To make the technical solution, implementation purpose, and beneficial effects of this invention clearer, a detailed description is provided below. It should be noted that the specific embodiments described below are only for illustrating this invention and do not constitute a limitation on the scope of protection of this invention.

[0025] The iron-containing solid waste used in the following examples is red mud, an industrial solid waste generated during the extraction of alumina in the aluminum industry. Example 1

[0026] This embodiment provides a ferrite catalyst, Fe3O4, for the alcoholysis of PET. The specific steps are as follows: (1) The iron-containing solid waste red mud was milled for 10 min, sieved to less than 200 mesh, and then dissolved in oxalic acid. It was stirred at 40℃ and 60 rpm / min until no more precipitate was formed. Then the solid and liquid were separated, and the obtained solid was dried at 105℃ for 24 h before use. (2) Place the dried solid in a muffle furnace and calcine it at 400°C for 6 hours to obtain the ferrite catalyst (Fe3O4).

[0027] (3) 5.0 g of waste PET plastic particles, 0.05 g of ferrite catalyst and 20 g of ethylene glycol were placed in a container, heated to 150°C, and stirred at a constant temperature for 2 h to obtain the BHET reaction product.

[0028] The reaction products were qualitatively and quantitatively analyzed by high performance liquid chromatography. The results showed that the conversion rate of PET was 75% and the yield of BHET was 65%. Example 2

[0029] The difference between this embodiment and Embodiment 1 is that the transition metal Mn is doped in the ferrite, while everything else is the same.

[0030] (1) The iron-containing solid waste red mud was milled for 10 min, sieved to less than 200 mesh, and then dissolved in oxalic acid. It was stirred at 40℃ and 60 rpm / min until no more precipitate was formed. Then the solid and liquid were separated, and the obtained solid was dried at 105℃ for 24 h before use. (2) Dissolve the transition metal manganese acetate [Mn(CH3COO)2] in water and add it to the reaction vessel with the solid obtained above at a transition metal manganese / iron molar ratio of 1:2. Add oxalic acid, adjust the pH to 3, and then stir and mix evenly. Heat the reaction at 80°C and 100 rpm / min. Dry the obtained reaction product to obtain the precursor. (3) The precursor prepared above is placed in a muffle furnace and calcined at 400℃ for 6 hours to obtain manganese ferrite catalyst (MnFe2O4).

[0031] (4) Place 5.0 g of waste PET plastic particles, 0.05 g of manganese ferrite catalyst and 20 g of ethylene glycol into a container, heat to 150 °C, and stir at a constant temperature for 2 h to obtain the BHET reaction product.

[0032] The reaction products were qualitatively and quantitatively analyzed by high performance liquid chromatography. The results showed that the conversion rate of PET was 93% and the yield of BHET was 85%. Example 3

[0033] The difference between this embodiment and Embodiment 1 is that the transition metal Cu is doped in the ferrite, while everything else is the same.

[0034] (1) The iron-containing solid waste red mud was milled for 10 min, sieved to less than 200 mesh, and then dissolved in oxalic acid. It was stirred at 40℃ and 60 rpm / min until no more precipitate was formed. Then the solid and liquid were separated, and the obtained solid was dried at 105℃ for 24 h before use. (2) Dissolve the transition metal copper acetate [Cu(CH3COO)2] in water and add it to the reaction vessel with the solid obtained above at a transition metal copper / iron molar ratio of 1:2. Add oxalic acid, adjust the pH to 3, and then stir and mix evenly. Heat the reaction at 80°C and 100 rpm / min. Dry the obtained reaction product to obtain the precursor. (3) The precursor prepared above is placed in a muffle furnace and calcined at 400℃ for 6 hours to obtain copper ferrite catalyst (CuFe2O4).

[0035] (4) Place 5.0 g of waste PET plastic particles, 0.05 g of copper ferrite catalyst and 20 g of ethylene glycol into a container, heat to 150 °C, and stir at a constant temperature for 2 h to obtain the BHET reaction product.

[0036] The reaction products were qualitatively and quantitatively analyzed by high performance liquid chromatography. The results showed that the conversion rate of PET was 79% and the yield of BHET was 69%. Example 4

[0037] The difference between this embodiment and Embodiment 1 is that the transition metal Zn is doped in the ferrite, while all other aspects are the same.

[0038] (1) The iron-containing solid waste red mud was milled for 10 min, sieved to less than 200 mesh, and then dissolved in oxalic acid. It was stirred at 40℃ and 60 rpm / min until no more precipitate was formed. Then the solid and liquid were separated, and the obtained solid was dried at 105℃ for 24 h before use. (2) Dissolve the transition metal zinc acetate [Zn(CH3COO)2] in water and add it to the reaction vessel with the solid obtained above at a transition metal zinc / iron molar ratio of 1:2. Add oxalic acid, adjust the pH to 3, and then stir and mix evenly. Heat the reaction at 80°C and 100 rpm / min. Dry the obtained reaction product to obtain the precursor. (3) The precursor prepared above is placed in a muffle furnace and calcined at 400℃ for 6 hours to obtain zinc ferrite catalyst (ZnFe2O4).

[0039] (4) Place 5.0 g of waste PET plastic particles, 0.05 g of zinc ferrite catalyst and 20 g of ethylene glycol into a container, heat to 150 °C, and stir at a constant temperature for 2 h to obtain the BHET reaction product.

[0040] The reaction products were qualitatively and quantitatively analyzed by high performance liquid chromatography. The results showed that the conversion rate of PET was 81% and the yield of BHET was 73%. Example 5

[0041] The difference between this embodiment and Embodiment 1 is that the transition metal Cr is doped into the ferrite, while everything else is the same.

[0042] (1) The iron-containing solid waste red mud was milled for 10 min, sieved to less than 200 mesh, and then dissolved in oxalic acid. It was stirred at 40℃ and 60 rpm / min until no more precipitate was formed. Then the solid and liquid were separated, and the obtained solid was dried at 105℃ for 24 h before use. (2) Dissolve the transition metal chromium acetate [(CH3COO)3Cr] in water and add it to the reaction vessel with the solid obtained above at a transition metal chromium / iron molar ratio of 1:2. Add oxalic acid and adjust the pH to 3. Then stir and mix evenly. Heat the reaction at 80°C and 100 rpm / min. Dry the obtained reaction product to obtain the precursor. (3) The precursor prepared above is placed in a muffle furnace and calcined at 400℃ for 6 hours to obtain chromium ferrite catalyst (CrFe2O4).

[0043] (4) Place 5.0 g of waste PET plastic particles, 0.05 g of copper ferrite catalyst and 20 g of ethylene glycol into a container, heat to 150 °C, and stir at a constant temperature for 2 h to obtain the BHET reaction product.

[0044] The reaction products were qualitatively and quantitatively analyzed by high performance liquid chromatography. The results showed that the conversion rate of PET was 83% and the yield of BHET was 72%. Example 6

[0045] The difference between this embodiment and Embodiment 1 is that the transition metal Co is doped in the ferrite, while all other aspects are the same.

[0046] (1) The iron-containing solid waste red mud was milled for 10 min, sieved to less than 200 mesh, and then dissolved in oxalic acid. It was stirred at 40℃ and 60 rpm / min until no more precipitate was formed. Then the solid and liquid were separated, and the obtained solid was dried at 105℃ for 24 h before use. (2) Dissolve the transition metal cobalt acetate [(CH3COO)2Co] in water and add it to the reaction vessel with the solid obtained above at a transition metal cobalt / iron molar ratio of 1:2. Add oxalic acid and adjust the pH to 3. Then stir and mix evenly. Heat the reaction at 80°C and 100 rpm / min. Dry the obtained reaction product to obtain the precursor. (3) The precursor prepared above is placed in a muffle furnace and calcined at 400℃ for 6 hours to obtain the cobalt ferrite catalyst (CoFe2O4).

[0047] (4) Place 5.0 g of waste PET plastic particles, 0.05 g of cobalt ferrite catalyst and 20 g of ethylene glycol into a container, heat to 150 °C, and stir at a constant temperature for 2 h to obtain the BHET reaction product.

[0048] The reaction products were qualitatively and quantitatively analyzed by high performance liquid chromatography. The results showed that the conversion rate of PET was 90% and the yield of BHET was 83%.

[0049] It should be noted that any parts not mentioned in this invention can be achieved by using or referencing existing technologies. The preparation method of the application is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of this application.

Claims

1. A method for preparing a transition metal-doped iron-containing solid waste catalytic material, characterized in that, Includes the following steps: (1) Physically screen or treat the iron-containing solid waste by disc (ball) milling, then dissolve it in organic acid, heat and stir until no more precipitate is formed, and obtain a suspension; (2) The suspension obtained in step (1) is subjected to solid-liquid separation, and the resulting solid is washed and dried for later use; (3) Dissolve the transition metal salt in water and add it to the reaction vessel with the solid obtained in step (2) at a transition metal M / iron molar ratio of 1:1~3. Add oxalic acid, adjust the pH to 2~4, and then stir and mix evenly. (4) The mixture from step (3) is heated to react, and the resulting reaction product is dried to obtain the precursor; (5) The precursor obtained in step (4) is placed in a muffle furnace for calcination to obtain a transition metal-doped ferrite catalyst.

2. The preparation method of a transition metal-doped iron-containing solid waste PET degradation catalytic material according to claim 1, characterized in that, In step (1), the iron content in the iron-containing solid waste is expressed as Fe2O3 ≥ 10 wt.%; the iron-containing solid waste includes one or more of steel slag, red mud, blast furnace slag, ferroalloy slag, iron-containing catalysts, and scrap steel.

3. The preparation method of a transition metal-doped iron-containing solid waste PET degradation catalytic material according to claim 1, characterized in that, In step (1), the organic acid is one of acetic acid, oxalic acid or citric acid; the heating and stirring are at 20~80℃ and the stirring rate is 5~100 rpm / min.

4. The preparation method of a transition metal-doped iron-containing solid waste PET degradation catalytic material according to claim 1, characterized in that, In step (2), the drying process is carried out at a temperature of 100±5℃ for 12~48h.

5. The preparation method of a transition metal-doped iron-containing solid waste PET degradation catalytic material according to claim 1, characterized in that, In step (3), the transition metal salt is Mn-containing... 2+ Cr 3+ Zn 2+ Cu 2+ or Co 2+ Metal salts.

6. The preparation method of a transition metal-doped iron-containing solid waste PET degradation catalytic material according to claim 1, characterized in that, In step (4), the heating reaction is carried out at 20~95℃ with a stirring rate of 50~200 rpm / min for 6~24h.

7. The preparation method of a transition metal-doped iron-containing solid waste PET degradation catalytic material according to claim 1, characterized in that, In step (5), the roasting temperature is 200~600℃ and the roasting time is 1-10h.

8. A transition metal-doped iron-containing solid waste catalytic material is prepared by the preparation method according to any one of claims 1 to 7.

9. The transition metal-doped iron-containing solid waste catalytic material of claim 8 is applied to the degradation of PET, characterized in that, The process includes the following steps: adding iron-containing solid waste catalyst material doped with transition metal, waste PET plastic and ethylene glycol into a reaction vessel for depolymerization and transesterification reaction, heating to 150~200℃, stirring at a constant temperature for 1~6h, to obtain the diethyl terephthalate (BHET) reaction product.

10. The application according to claim 9, characterized in that, The mass ratio of the transition metal-doped iron-containing solid waste catalytic material to waste PET plastic is 0.02~0.3:1, and the mass ratio of the waste PET plastic to ethylene glycol is 1:1~10.

Citation Information

Patent Citations

  • Method for catalysis and alcoholysis of polyethylene terephthalate by ferromagnetic substance

    CN101735061A

  • Preparation method of supported transition metal catalyst utilizing iron tailings as carrier and method for degrading organic pollutants

    CN103464166A

  • Method for preparing VOCs catalyst by using iron-containing solid waste

    CN110404554A

  • Method for preparing doped nanometer iron oxide by using iron-containing waste

    CN110540244A

  • Method for preparing doped nano zinc ferrite by using ferriferous wastes

    CN110560070A

Cited By

  • Preparation method of metal iron-niobium catalyst and application of alcoholysis waste plastic

    CN122399826A